Local Knowledge Suggests Significant Wildlife Decline and Forest Loss in Insurgent Affected Similipal Tiger Reserve, India. (June 2013) - Sahoo, Sasmita; Puyravaud, Jean-Philippe; Davidar, Priya
Similipal Tiger Reserve is a large insurgent-affected protected area (PA) located in the northern Eastern Ghats, India, with a resident tribal population of about 12, 500. In 2007-08, we carried out a survey of conservation attitudes among 217 men and women (<20 years old) and documented their perceptions of wildlife and forest decline over a 20-year period from 1997-2007. Using data from the Forest Survey of India, we ascertained the decrease in forest cover (<40%), and using available census information we assessed tiger status over this period. Most of the respondents were primarily agriculturists (79%), and all households collected fuel-wood from the forest; 13% hunted and 49% fished. The majority of the respondents (80%) agreed that trees had disappeared, and 90% agreed that the tiger and elephant had disappeared. Respondents' recollections of Bengal tiger and Asian elephant sightings over a 20-year period indicated a drastic decline in their numbers, and perceptions of forest loss were supported by assessments of changes in dense forest cover indicating an annual deforestation rate of 1.577% yr −1 over a 20-year period, or loss of 274 km 2 of dense forest. This suggests that forest dwelling communities have an acute awareness of disappearing forests and wildlife, and informant-based surveys can be indicative of the status of wildlife and forests in situations such as Similipal, where ecological studies are problematic due to civil conflict.